INSTYTUCJONALNE UWARUNKOWANIA STRATEGII ROZSZERZENIA UNII EUROPEJSKIEJ - Barcz, Jan (Wydział Prawa i Administracji UAM, 2009)
Continuation of the EU enlargement depends, to some extent, on how well the EU institutional system is prepared to “absorb” new members. The main factors that influence this “absorption capability” are, on the one hand, the weakening willingness, or readiness, of the existing member states to take on new members, and the generally poor, albeit differentiated, level of preparation of individual candidate states for EU membership, on the other. For most candidates the requirements o f adherence to the fundamental principles of a democratic state are still a real challenge. The paper analyses three main institutional questions that play a major role in the adjustment processes when new member states gain EU membership (and which also are the key issue o f the EU reform). They include the qualified majority voting in the EU Council, the allocation of seats in the European Parliament, and the determination of the composition of the European Commission. The analysis of the above leads to a conclusion that although the enforcement of the Lisbon Treaty would undoubtedly facilitate further continuation o f the EU enlargement strategy, even under the current Nice Treaty the accession of the West Balean states should pose no real problems. In the case of Turkey, or the Ukraine, however, some basic elements of the “Lisbon Treaty” package would need to be renegotiated.
INSTITUTIONAL CONDITIONS OF THE EUROPEAN UNION ENLARGEMENT STRATEGY